Seguindo o fio: a tapeçaria artística tramada no Rio Grande do Sul - Secco, Lorilei (2023)
Having noted the scarcity of studies on textile art in Rio Grande do Sul, artistic tapestry was established as the central theme of this research, incorporating the following problem: which historical-artistic panorama can be traced based on the understanding of trajectories and textile works created by five artists from Rio Grande do Sul between the 1970s and 1990s? The corpus of analysis was made up of Yeddo Titze, Ivandira Dotto, Zoravia Bettiol, Carla Diehl Obino and Liciê Hunsche. Thus, the thesis was formed that, based on a historiographical and artistic investigation of the production of tapestries in Rio Grande do Sul, prioritizing the precursor centers formed in Porto Alegre and Santa Maria, an overview, albeit partial, of the textile art in dialogue with the current cultural system. In this way, tapestry as a segment of textile language would constitute a contributing and legitimizing component of an artistic movement that occurred in the state during this period. Derived from the problem, the geographical delimitation of the state of Rio Grande do Sul was established as a spatial delimitation, which also coincides with that of the region in terms of spaces in Porto Alegre and Santa Maria. Concerning the time period, the 1970s, 1980s and 1990s were prioritized as they were those with the most significant production and circulation of works and related artistic events. Also paying attention to coherence in historiographical procedures, the study is based on the dimension of New Cultural History (NHC), with an approach anchored in Regional History, whose domain is located in the broad area of ​​Art History, specifically focused on textile language. Within this, the theme of woven artistic tapestries, which in contemporary times also receive other names: objects, sculptures or installations. Methodologically, this is a qualitative, bibliographic, exploratory and documentary research, mediated through images that, among many functions, participate here as information and the possibility of visual access to the works. To this end, the basis was guided, above all, by the writings of Andrade (1978); Barros (2007, 2008, 2013); Bourdieu (1983, 1989, 1996, 2007); Brites (1991, 2007, 2012, 2015); Bulhões (2007, 2014, 2020); Burke (1995, 2003, 2008, 2011); Carvalho (2007a and 2007b); Cáurio (1985); Chartier (1995); Foletto and Bisognin (2001); Gradim (2015, 2016, 2018); Grippa (2017, 2021, 2023); Mattar (2011, 2013, 2020); Pesavento (2004, 2008); Ramos (2007, 2017); Simioni (2007a, 2007b); Zattera (1988); Zielinsky (1985), as well as other references that contributed to specific aspects of development. Especially in Rio Grande do Sul, the occurrence of a legitimate artistic movement linked to textiles, especially tapestry, with a limited duration, starting around 1960, reaching its peak in the 80s and decline in the 1990s was confirmed. In this particular time and space, a group of artists shared common trends, adopting exclusive cultural practices, as a way of affirming identity and searching for symbolic capital in the field of art. They influenced each other by creating textile works and working to promote their artistic ideas, occupying spaces that had never been reached before. A legacy that contributed to the history of art in the state and reverberates to this day.